Environmental, social, and governance performance and financial impacts: Comparative analysis of companies in Asia - Kenichi Yoshida; Jun Xie; Shunsuke Managi; Satoru Yamadera (Asian Development Bank (ADB), 2024)
This study investigated environmental, social, and governance (ESG) performance and its financial impacts across 38 economies from 2013 to 2022, with a special focus on firms in Asia. The main findings are as follows. First, notable disparities in ESG assessments were found across major rating agencies due to a lack of commensurability in ESG elements and evaluation methods. Second, the multilevel model analysis demonstrated considerable space for enhancing the ESG performance of companies in Asia, in contrast to that of their counterparts in Europe. Notably, the ESG practices of firms in Southeast Asia have stronger positive relationships with financial performance. Finally, inclusive wealth significantly moderates the financial impacts of ESG practices and can serve as a valuable sustainability indicator at the national level to inform ESG practices specific to different regions.
Keywords: M14; M41; O16; 330; ESG performance; comparative CSR; inclusive wealth; multilevel regression model